Trajetórias e determinantes do alto risco cardiovascular de 30 anos entre participantes de uma coorte brasileira (Estudo CUME) - Renata Soares Passinho (2023)
Introduction: Cardiovascular diseases are the main public health problem worldwide. Therefore, the assessment of cardiovascular risk, with the identification of its risk and protection factors and their trajectories over time, are important for proposing, consolidating and implementing measures to prevent the occurrence of cardiovascular diseases. General objective: To analyze the 30-year trajectory and determinants of high cardiovascular risk in participants of the Cohort of Universities of Minas Gerais (CUME Study). Methods: Initially, an integrative literature review was performed, followed by two prospective cohort studies. A) Article 1 – integrative review of the literature on the estimation of high cardiovascular risk and its associated factors, carried out in the databases Medical Literature Analysis and Retrievel System Online, Web of Science, Excerpta Medica Database, Cumulative Index to Nursing and Allied Health Literature and the Virtual Health Library portal; B) Article 2 – Prospective open cohort developed with 2,854 participants of the CUME Study, which is a multicenter research conducted with graduates from seven federal public institutions of higher education in the State of Minas Gerais since 2016. The incidence of high cardiovascular risk at 30 years was calculated using the Framingham score and its determinants were estimated using hierarchical multivariate analysis by the Cox regression technique; C) Article 3 – Prospective closed study developed with 1,286 participants from CUME, who answered the baseline questionnaire in 2016, the two-year follow-up questionnaire in 2018 and the four-year follow-up questionnaire in 2020. The risk Cardiovascular was assessed using the 30-year Framingham score. The identification of cardiovascular risk trajectories was performed using the latent class growth modeling technique using the normal censored model. The analysis of the factors independently associated with each of the trajectories was conducted using the multinomial logistic regression technique. Results: Article 1 – 13 articles were selected with one or more factors associated with high cardiovascular risk, according to the Framingham score over 10 years. No article investigated the factors associated with 30-year high cardiovascular risk. Article 2 – After an average of 2.62 years of follow-up, the incidence of high cardiovascular risk at 30 years was 8.1 cases/1,000 person-years in females and 20.2 cases/1,000 person-years in males. Male sex (Hazard Ratio – HR: 2.34; 95% CI: 1.58 - 3.46), work (HR: 2.13; 95% CI: 1.13 - 3.99), high food intake processed foods (HR: 2.44; 95% CI: 1.21 - 4.90) and being physically active (HR: 0.63; 95% CI: 0.41 - 0.98) were independently associated with high cardiovascular risk 30 years old; Article 3 - Three 30-year cardiovascular risk trajectories were identified: Low-Low (68.3%), Medium-Medium (26.2%) and High-High (5.5%). Over time, cardiovascular risk showed a slight increase for the Low-Low trajectory (2.9%), a moderate increase for the Medium-Medium trajectory (7.6%) and a high increase for the High-High trajectory (13%). Being male, living in a stable relationship, having moderate and high consumption of ultra-processed foods were positively associated with Medium-Medium and High-High cardiovascular risk trajectories. Also, having professional training outside the health area and being working were positively associated with the Medium-Medium cardiovascular risk trajectory, while being physically active was negatively associated with the High-High cardiovascular risk trajectory. Conclusion: Few studies were conducted to assess the 30-year high cardiovascular risk, and none of them estimated factors associated with the outcome. Our scientific findings indicated that practicing physical activity reduces the incidence of 30-year high cardiovascular risk. Men, people who work and with a high consumption of processed foods should be monitored with greater caution, as they were more susceptible to the occurrence of the high cardiovascular risk of 30 years. Young adults with better socioeconomic status have a 30-year trajectory of low cardiovascular risk, however, there is a tendency for this trajectory to worsen over time due to bad lifestyle habits. Thus, it is essential to implement prevention strategies to avoid cardiovascular disease.